Virtual water trade and bilateral conflicts. (December 2017) - De Angelis, Enrico; Metulini, Rodolfo; Bove, Vincenzo; Riccaboni, Massimo
Highlights: In light of growing water scarcity, virtual water has been an active area of debate. We analyze the role of virtual water in affecting the odds of militarized disputes. Using virtual water trade data we find that trade openness reduce the odds of wars. Results are consistent with the concept of opportunity cost and loss of trade gains. Effect of virtual water is comparable to that of oil and gas, a strategical resource. Abstract: In light of growing water scarcity, virtual water, or the water embedded in key water-intensive commodities, has been an active area of debate among practitioners and academics alike. As of yet, however, there is no consensus on whether water scarcity affects conflict behavior and we still lack empirical research intending to account for the role of virtual water in affecting the odds of militarized disputes between states. Using quantitative methods and data on virtual water trade, we find that bilateral and multilateral trade openness reduce the probability of war between any given pair of countries, which is consistent with the strategic role of this important commodity and the opportunity cost associated with the loss of trade gains. We also find that the substantive effect of virtual water trade is comparable to that of oil and gas, the archetypal natural resources, in determining interstate conflicts' probability.